Pit lake water quality and hydrology : Insights from case studies and modelling of pit lakes in northern Sweden - Paulsson, Oscar (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2021)
As extraction techniques are improving an increased number of low grade deposits can be economically mined. However, this also means that the number of open pit mines will increase and as a result the number of pit lakes as well. This is of environmental concern as the pit lakes, depending on the geology and other factors, potentially can have a negative impact on surrounding ecosystems, e.g. through high metal concentrations, low pH, and by affecting the hydrologic system. Sweden has a long history of mining and is one the largest metal suppliers in Europe, and many of the mines are located in the northern part of the country. The project aim was to better understand and be able to predict pit lake water quality and some of the underlying processes affecting it, with a focus on cold climates, where temperatures are low and the lakes are ice covered for prolonged periods of time. The following field measurements were conducted in the Laver and Åkerberg pit lakes: 1) minewall stations measuring metal leaching rates from pit walls, 2) oxygen and hydrogen isotopic composition of precipitation and pit lakes to better understand pit lake hydrology (including also the Udden and Rävlidmyran pit lakes), 3) a nutrient limitation and metal uptake experiment in the Åkerberg pit lake, and 4) a continuously measuring buoy installed in the Laver pit lake where short term fluctuations in water quality parameters could be observed. A bathymetric map of the Åkerberg pit lake was also generated during the project. Additionally, modelling of the Rävlidmyran pit lake was conducted based on three different climate scenarios. Measurements of water quality parameters showed that both the Laver and Åkerberg pit lakes have relatively good water quality, pH 6.1–7.4, specific conductivity 41–352 μS/cm and pH 7.6-7.7, specific conductivity 137–140 μS/cm, respectively, and low concentrations of metals. Algal growth was successfully stimulated in microcosms in the Åkerberg pit lake, through addition of the nutrients N and P in combination. ...